2016
DOI: 10.1542/peds.2015-1766
|View full text |Cite
|
Sign up to set email alerts
|

Physical Examination Findings Among Children and Adolescents With Obesity: An Evidence-Based Review

Abstract: Overweight and obesity affects 1 in 3 US children and adolescents. Clinical recommendations have largely focused on screening guidelines and counseling strategies. However, the physical examination of the child or adolescent with obesity can provide the clinician with additional information to guide management decisions. This expert-based review focuses on physical examination findings specific to children and adolescents with obesity. For each physical examination element, the authors define the finding and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 140 publications
0
8
0
2
Order By: Relevance
“…The reference values presented in this study could be used by the Iranian physicians to identify children and adolescents with abnormal NC values; considering the significant risks of future cardiovascular and metabolic disorders associated with higher NC ( 26 - 29 ), preventive measures could be taken for these subjects predisposed to the aforementioned conditions. However, further studies are needed to determine the optimal cut-off points for prediction of cardiovascular, pulmonary, and metabolic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The reference values presented in this study could be used by the Iranian physicians to identify children and adolescents with abnormal NC values; considering the significant risks of future cardiovascular and metabolic disorders associated with higher NC ( 26 - 29 ), preventive measures could be taken for these subjects predisposed to the aforementioned conditions. However, further studies are needed to determine the optimal cut-off points for prediction of cardiovascular, pulmonary, and metabolic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Children with obesity commonly have a mechanical deficiency in the medial tibial growth plate which can result in the bowing of the tibia [ 23 , 28 ], known as tibia varus or Blount’s disease. Children with obesity can also experience slipped capital femoral epiphysis around skeletal maturity, where the femur is rotated externally from the growth plate causing pain and the inability to walk [ 22 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies using children's data in communities have also found this conclusion [26,27]. Although no empirical evidence was provided, some studies conducted in western countries recommended that monitoring children's BMI is an effective approach to reduce the risk of obesity [28]. Only the US Preventive Services Task Force (USPSTF) found evidence that screening and behavioral interventions for obesity in children 6 years and older can contribute to the improvements in weight status, and the magnitude of this benefit is greater than with pharmacotherapy interventions [29].…”
Section: Introductionmentioning
confidence: 90%